EDUKASI DAN KONSULTASI MP-ASI UNTUK PENCEGAHAN DIARE ANAK DI LINGKUNGAN PUSKESMAS KEMIRI MUKA DEPOK - Muhammad Rizki Purnama; Ibnu Malkan Bakhrul Ilmi; Nur Intania Sofianita (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2022)
Diarrhea is a health problem due to infection in the gastrointestinal tract, which is characterized by changes in the consistency of feces to liquid and an increase in the frequency of stool disposal more than three times a day. Breast milk positively impacts the baby's immune system so that it can reduce the possibility of infection and the incidence of diarrhea. Giving complementary feeding (MP-ASI) at an early age (< 6 months) can cause infection in the baby's digestive system and lead to diarrhea. The prevalence of diarrhea in RW 09 mothers reached 76%, the application of maternal hygiene was 76.2%, the coverage of exclusive breastfeeding was 85.7%, and early complementary feeding was 52.4%. The activity was carried out on 4 – 30 September 2021. The material provided in the education includes understanding MP-ASI, the benefits of giving MP-ASI, the principle of giving MP-ASI, the impact of giving MP-ASI early, texture, frequency, and amount of MP-ASI. Community service that has been carried out is MP-ASI education using booklets and nutrition consultations. Univariate analysis was conducted to describe the incidence of diarrhea, hygiene behavior, exclusive breastfeeding, early complementary feeding, and the characteristics of mothers and babies. Bivariate analysis to determine changes in knowledge before being given education with after being given education. Bivariate analysis was processed using the Wilcoxon test. The results of the data analysis showed that the mother's level of knowledge regarding complementary feeding increased (p=0.000). The results of the nutrition consultation were obtained; namely, the lack of variety in the provision of complementary foods, babies were only given fruit puree and instant baby porridge, lack of knowledge of complementary foods recipes, and babies' difficulty accepting new foods ABSTRAK Diare merupakan masalah kesehatan akibat infeksi pada saluran cerna yang ditandai dengan perubahan konsistensi feses menjadi cair serta peningkatan frekuensi pembuangan feses lebih dari tiga kali dalam satu hari. ASI memberikan dampak positif terhadap sistem imun bayi, sehingga dapat menurunkan kemungkinan infeksi dan kejadian diare. Pemberian makanan pendamping ASI (MP-ASI) pada usia dini (< 6 bulan) dapat menyebabkan infeksi pada sistem pencernaan bayi dan berujung pada kejadian diare. Prevalensi diare ibu RW 09 mencapai 76%, penerapan hygiene Ibu sebesar 76.2%, cakupan ASI eksklusif sebesar 85.7% dan pemberian MP-ASI dini sebesar 52.4%. Kegiatan dilaksanakan pada 4 – 30 September 2021. Materi yang diberikan dalam edukasi meliputi pengertian MP-ASI, Manfaat pemberian MP-ASI, Prinsip pemberian MP-ASI, Dampak pemberian MP-ASI dini, Tekstur, frekuensi dan jumlah MP-ASI. Pengabdian masyarakat yang telah dilakukan yaitu edukasi MP-ASI menggunakan booklet dan konsultasi gizi. Analisis univariat dilakukan untuk melihat gambaran kejadian diare, perilaku hygiene, pemberian ASI Eksklusif, pemberian MP-ASI dini serta karakteristik Ibu dan Bayi. Analisis bivariat untuk mengetahui perubahan pengetahuan sebelum diberikan edukasi dengan setelah diberikan edukasi. Analisis bivariat diolah dengan menggunakan uji Wilcoxon. Hasil analisis data menunjukkan tingkat pengetahuan Ibu mengenai pemberian MP-ASI meningkat (p=0,000). Hasil konsultasi gizi diperoleh yaitu kurangnya variasi pemberian MP-ASI, bayi hanya diberi puree buah dan bubur bayi instan, kurangnya pengetahuan resep MP-ASI, bayi sulit menerima makanan baru.